2018
DOI: 10.1242/dmm.032482
|View full text |Cite
|
Sign up to set email alerts
|

Feeding difficulties, a key feature of the Drosophila NDUFS4 mitochondrial disease model

Abstract: Mitochondrial diseases are associated with a wide variety of clinical symptoms and variable degrees of severity. Patients with such diseases generally have a poor prognosis and often an early fatal disease outcome. With an incidence of 1 in 5000 live births and no curative treatments available, relevant animal models to evaluate new therapeutic regimes for mitochondrial diseases are urgently needed. By knocking down ND-18, the unique Drosophila ortholog of NDUFS4, an accessory subunit of the NADH:ubiquinone ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 68 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…In patients, mutations in subunits of complex I can cause isolated or combined OxPhos enzymatic activity disturbances. To determine whether knocking down of Drosophila CI subunits leads to comparable defects, we measured the activity of the five OxPhos complexes in the adult KD models and compared these to the complex activities of their isogenic controls and to previous data obtained for the S4 subunit (Foriel et al, 2018). Without any exception, all models that were sufficiently viable to allow collection of adult progenies presented a strong reduction of CI activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In patients, mutations in subunits of complex I can cause isolated or combined OxPhos enzymatic activity disturbances. To determine whether knocking down of Drosophila CI subunits leads to comparable defects, we measured the activity of the five OxPhos complexes in the adult KD models and compared these to the complex activities of their isogenic controls and to previous data obtained for the S4 subunit (Foriel et al, 2018). Without any exception, all models that were sufficiently viable to allow collection of adult progenies presented a strong reduction of CI activity.…”
Section: Resultsmentioning
confidence: 99%
“…Other complexes activities were either significantly increased (CII in S7/Actin/25°C, CIII in all models, CIV in S7/Actin/25°C and S7/da/25°C) or significantly decreased (CV in S4/Actin/25°C). The numerical values are provided in Supplementary Table S1 (S4/actin/28°C graph reproduced/adapted with permission from Foriel et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Vglut2:Ndufs4cKO and Gad2:Ndufs4cKO mice had reduced lifespan and body weight, which was accompanied by a decrease in food intake, which are common clinical signs that appear in Leigh Syndrome patients 1,30 . Recent reports have shown that neuronal cell-specific NDUFS4 knock down in Drosophila also leads to severe feeding abnormalities and premature death 31 . Our results indicate a conserved role for neurons in the onset and progression of the pathological condition of global Ndufs4 deficiency and reveal that both glutamatergic and GABAergic systems contribute to the growth and lethality phenotype.…”
Section: Discussionmentioning
confidence: 99%